Hubungan Tingkat Nyeri Sendi dengan Aktivitas Fisik pada Lansia Gangguan Sendi - Muna, Naila Dhiya’ul; Hartati, Elis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the relationship between the level of joint pain and physical activity in elderly with joint disorders in the Genuk Community Health Center. The method used is non-experimental quantitative with a cross-sectional approach and using the bivariate spearman rank test. The instruments used in this research were the Numeric Rating Scale (NRS) and the Physical Activities Scale of Elderly (PASE) questionnaire. Results of research showed that 35.1% of elderly experienced unbearable severe joint pain and 59.2% of elderly did less physical activity. The results of the spearman test show that there is a significant relationship between the level of joint pain and physical activity in elderly with joint disorders with p = 0.000 and rs = -0.847. The research conclusion is that the higher the intensity of joint pain in the elderly, the lower the physical activity or the less physical activity the elderly, the intensity of joint pain increases. Keywords: Elderly, Joint Pain, Physical Activity